Profile of neonatal mortality in special newborn care unit of tertiary care hospital - Sharma, Ashutosh Kumar; Gaur, Ajay (International Journal of Contemporary Pediatrics, 2019)
Background: In India presently around 8 million LBW infant are born each year. India accounts for 24% of global neonatal mortality. Improving NMR is an essential component of reducing U-5MR. The aim of this study was to determine the causes of morbidity and mortality in neonates admitted in our hospital. Methods: This study was conducted at SNCU of Kamala Raja Hospital, Gwalior providing level III neonatal care. This is a retrospective hospital based observational study. Data from SNCU online database were taken for a period of 3 year from March 2016 to March 2019. Data obtained included sex, birth weight, Gestation age, morbidity profile, Diagnosis, and Mortality profile, Duration of stay and outcome. Categorical variables were tabulated and Statistical analysis was done. Results: A total of 12,027 neonates were recruited, 63.07% were males and 36.92% were females. 54.87% were extramural, while 45.13% were intramural neonates. Prematurity was the most common morbidity 56.98% in the admitted neonates. Major contributors to the neonatal morbidity were Birth asphyxia (24.61%), others (21.60%), Respiratory Distress(14.06%), Sepsis(13.77%). The mortality rate in the present study is 25.45%. Major contributors for neonatal mortality includes Respiratory distress (37.76%), Birth Asphyxia (26.75%), Sepsis(13.91%). Mortality was more in out born babies 33.03% compared to inborn babies 22.03%. Conclusions: Improving antenatal care, more deliveries at institutions with SNCU facility, improved access to health facility, early identification of danger signs, timely referral of high risk cases, capacity building, can reduce neonatal mortality and its complications.